2014
DOI: 10.1039/c4cc05614k
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic dual-targeting hydrogel improves targeting and anticancer effect of Taxol in vitro and in vivo

Abstract: A synergistic dual-targeting molecular self-assembly hydrogel was designed with estrone (Et) and Arg-Gly-Asp (RGD) peptide. Confocal imaging in vitro and real-time visualization in vivo researches were carried out to evidence enhanced targeted delivery and anticancer effect of Taxol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…A hydrogel‐based delivery system functionalized with estrone and RGD peptide ligands (Et‐peptide‐Taxol hydrogel) was devised for paclitaxel delivery to breast carcinoma via EGFR and α v β 3 integrin receptor‐mediated endocytosis . At concentrations of 50 and 100 n m , Et‐peptide‐Taxol hydrogel DDVs developed by Shu et al.…”
Section: Ddv Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A hydrogel‐based delivery system functionalized with estrone and RGD peptide ligands (Et‐peptide‐Taxol hydrogel) was devised for paclitaxel delivery to breast carcinoma via EGFR and α v β 3 integrin receptor‐mediated endocytosis . At concentrations of 50 and 100 n m , Et‐peptide‐Taxol hydrogel DDVs developed by Shu et al.…”
Section: Ddv Optimizationmentioning
confidence: 99%
“…In vivo, the Et‐peptide‐Taxol hydrogel was found to selectively accumulate in tumor tissue and bladder in MCF7 tumor bearing mice. Full renal clearance was achieved by 48 h, at which time Et‐peptide‐Taxol hydrogel particles were still highly retained within tumor tissue …”
Section: Ddv Optimizationmentioning
confidence: 99%
“…Zhong and coworkers designed a synergistic dual-targeting hydrogel that was able to transport drugs for specifically targeting tumors. [295] Experimental results revealed the accumulation of hydrogel within the cancer cells in vitro as well as in breast tumor in vivo . They confirmed that the estrone and RGD peptide acted as the tumor-targeting moieties and contributed to the selective accumulation of the hydrogel in the breast tumor.…”
Section: Applications Of Supramolecular Biofunctional Materialsmentioning
confidence: 99%
“…As discussed in the previous section, supramolecular hydrogels have already shown promises as possible cancer drug delivery systems. [277, 295, 297300] In this section we discuss the recent development in the use of supramolecular hydrogelators themselves as innovative anticancer therapeutics.…”
Section: Applications Of Supramolecular Biofunctional Materialsmentioning
confidence: 99%
“…Compared with intravenous injection of clinically used Taxol® with four times the dosage, this hydrogel could inhibit tumor growth more efficiently by a single dose of intratumor administration, which suggested the big potential of this novel gelation system of Taxol for cancer therapy. In one of our previous articles, a novel synergistic dual‐targeting molecular self‐assembly hydrogel of Taxol was developed by conjugation with estrone and RGD peptide, which transported drugs, specifically targeted tumors, and penetrated breast cancer cells. Confocal imaging in vitro and real‐time visualization in vivo were carried out to evidence enhanced targeted delivery and anticancer effect of Taxol.…”
Section: Introductionmentioning
confidence: 99%